Digital Comics Based on Numeracy Literacy to Increase Reading Interest in Primary School High Grades - Bella, Bella Emilia Putri; Siti Nur Hazizah; Kavita Febian; Dede Endang Mascita; Mudopar (Jurnal Pendidikan Indonesia, 2024)
This research was motivated by the low reading interest of high-class students. This research aims to develop learning media in the form of digital comics based on numeracy literacy that can increase students' interest in reading. The type of research used is Research and Development (R&D) with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were high-class students, while the data was collected through questionnaires before and after the implementation of digital comics and through validation by technology experts. The data were analyzed using quantitative descriptive techniques. The results of the study showed an increase in students' interest in reading after using digital comics. The validation of technology experts showed that 95% stated that the comic material was in accordance with the students' comprehension ability, 90% assessed the language used as appropriate, and 98% stated that digital comics were effective in increasing reading interest. In conclusion, digital comics based on numeracy literacy can be an effective solution to increase students' interest in reading. This research has implications for the development of interactive learning media to improve literacy among elementary school students.